Pista sa Poblacion augmenting festival districts through spatial and generative landscape tools – as applied in Bacolod’s Masskara Festival - Lumaniog, Paulo Nico P.; Cathe Desiree S. Nadal; Vic L. Dul-loog (Quezon City College of Architecture, University of the Philippines Diliman, 2025)
Urban growth is reshaping Philippine festival settings, as seen in the MassKara Festival’s shift from Bacolod’s historic Poblacion district to emerging urban districts (EUDs). Once central to pedestrian activity, trade, and cultural gatherings, the Poblacion’s spatial and cultural fabric is being altered by decentralization and redevelopment.
This study responds by integrating Landscape Urbanism and Generative Design Process, using Space Syntax and Public Participation GIS (PPGIS) to analyze festivalgoer interactions with streetscapes, plazas, and vendors. Ethnographic observation and urban analysis highlight how spatial fragmentation impacts cultural continuity and accessibility.
To address these shifts, the research incorporates AI—specifically large language models (LLMs)—as interpretive and generative tools within the design process. AI aids in framing theoretical insights, synthesizing data, and constructing spatial typologies grounded in both local context and festival dynamics.
The result is a set of adaptive festival landscape typologies that enhance navigability, inclusivity, and cultural integrity amidst urban transformation. The "Festivalscapes" offer data-informed design solutions that improve accessibility, mobility, and environmental resilience for diverse stakeholders.
By fusing landscape architecture, AI, and spatial analytics, the study offers a scalable, forward-thinking approach to preserving intangible heritage while reimagining festival spaces for a more equitable, resilient urban future.
Include appendices
Thesis (Bachelor of Landscape Architecture) -- University of the Philippines Diliman
Keywords: Festivals -- Bacolod; Artificial Intelligence -- Landscape architecture